Prototipe Sistem Rekomendasi Film Indonesia Menggunakan Pendekatan Content Based Filtering dan Metode Vector Space Model - Theo Santoso, Daniel; Atina, Vihi; Hartanti, Dwi (Infotek: Jurnal Informatika dan Teknologi, 2024)
Film represents a combination of narrative and cinematographic aspects in an audio-visual form. Films also provide an engaging visual, auditory, and emotional experience. The film industry in Indonesia has shown significant growth. In 2015, cinema audiences numbered 16.2 million, increasing to 51.2 million in 2019. The COVID-19 pandemic caused a drastic decline in the number of viewers, with only 4.5 million in 2021. However, the industry quickly recovered, reaching 54.07 million viewers in 2022 and 55 million in 2023, and is projected to reach 60 million in 2024. With the increasing availability of films and streaming platforms, finding movies that match user preferences often becomes a challenge. This study proposes a film recommendation system using the Content-Based Filtering method and the Vector Space Model to help users more easily find movies that match their preferences. Content-Based Filtering recommends films based on content similarity, while the Vector Space Model measures content similarity using metrics such as cosine similarity or euclidean distance. Based on experiments using 20 sample films, the results show that the designed system can provide accurate and precise movie recommendations based on keywords provided by users. The film "Pengabdi Setan 2: Communion" has the highest similarity score of 0.3018, followed by "Nana," "Menjelang Magrib," "Jailangkung: Sandekala," and "Qorin," with similarity scores of 0.0865, 0.0138, 0.0136, and 0.0125, respectively